The prevalence of snoring and sleep apnoea symptoms reported by adult patients in Johannesburg urban general practice. - Rouhani-N, Mary M (My University, 2014)
The prevalence of Obstructive sleep apnoea (OSA) has never to date been researched in South Africa. OSA is characterized by recurrent pharyngeal airway collapse during sleep, snoring and daytime sleepiness. It is diagnosed in 4% of men and 2% of women between the ages o f 30 and 60 in the USA, and is associated with increased morbidity and mortality. This cross sectional descriptive study o f adult patients was undertaken to examine the prevalence of OSA symptoms reported by patients in urban general practice in Johannesburg. A total o f 304 self administered questionnaires were obtained for analysis. Snoring prevalence was 48.6% with increasing prevalence over a five year period (prevalence rates increased from 43.9% five years ago to a current prevalence of 48.6%). The prevalence of witnessed apnoeas, restless sleep and gasping were noted to be 12.4%, 44.6% and 11.8% respectively. 68% o f men and 32.5 % of women snored and prevalence rates were found to increase with increasing age. A significant association was also found between OSA symptoms and comorbidities, e.g., hypertension and depression. Based on the findings o f this study OSA appears to be a significant problem in South Africa. Routine screening o f patients for OSA seems warranted, and doctors need to be made aware o f these statistics.